The Constribution of Reading Web-Based Scientific English Articles on English Proficincy of English Department Students Riau University â Indonesia - Hadriana, Hadriana; Mahdum, Mahdum; Gultom, E. (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Having a good reading skill will add values to the students in terms of learning the language itself and in completing a paper or a final task. To complete the final task, the students need to read a lot of scientific articles, whether printed or web-based, for references. The objetive of this descriptive research is to analyze whether there is any contribution of reading web-based scientific English articles on the students`English proficiency. 50% of students of English Department - FKIP Riau University who are sitting in semester 7 and 9 are randomly choosen as the samples of this research. The instruments being used are the questionnaire and TOEFL Test. The data analysis shows that the contribution of reading web-based scientific English articles on the studentsâ English proficiency is 4.8%. It means that there is a significant contribution of reading web-based scientific English articles on the English proficiency of the students.